The Role of Otoritas Jasa Keuangan (Financial Services Authority) in Supervising Sharia Banking Products in Indonesia - Ida Hanifah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The number of cross-sectoral issues in the financial services sector including Islamic banking, which includes moral hazard measures, lack of optimal protection of financial services, and the disruption of financial system stability increasingly encourage the need for the establishment of a supervisory institution in the integrated financial services sector. The source of moral damage in the management of the economy encourages the establishment of newsupervision institutions, more accountable and has a tighter function in overseeing the financial system so that it can better guarantee the achievement of financial system stability. Based on that, Financial Services Authority was formed. Various regulations that have been and will be made by the Financial Services Authority related to Islamic banking are expected to be able to provide protection for the Islamic banking industry as well as spur the development of Islamic banking in Indonesia. More comprehensive and effective supervision of sharia banking is needed along with the increase in market players, product / service variants, and increasingly innovative and complex technological advancements. During this time the existence of Financial Services Authority for Islamic banking has not felt its existence. Financial Services Authority Law is still silent on sharia-based financial services.